Dog breath! : the horrible trouble with Hally Tosis - Pilkey, Dav, 1966- (Blue Sky Press, 1994)
Hally, the Tosis family dog, has such bad breath that Mr. and Mrs. Tosis plan to give her away, until she proves to be an invaluable watchdog.